Pengaruh Bonus, Pembiayaan Utang, Penghindaran Pajak dan Pertumbuhan Laba Terhadap Kualitas Laba - Desi Andrianti; Novita Indrawati; Al Azhar L; Rofika; Zirman (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
This study aims to determine the effect of bonuses, debt financing, tax avoidance, dan profit growth on earnings quality in 2017-2021 companies (Study of Manufacturing Companies listed on the Indonesia Stock Exchange). This research uses quantitative research methods. Sources of data that researchers use is secondary data. The secondary data that the researcher uses are in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange which are obtained through the links www.idx.co.id and related websites other. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020, totaling 220 companies. The sampling technique used in this article is purposive sampling with a total of 65 companies with 5 years and a total of 325 company data. The analytical method used in this research is multiple regression analysis using IBM SPSS Statistics Ver.  27. Based on the results of the study, debt financing and tax avoidance have an effect on earnings quality, while bonuses and profit growth have no effect on earnings quality.